Fiscal federalism in Germany - Yannick Bury; Lars P. Feld (Albert-Ludwigs-Universität Freiburg, Institut für Allgemeine Wirtschaftsforschung, Abteilung für Wirtschaftspolitik und Ordnungsökonomik, 2020)
[...] In view of this development of fiscal federalism in Germany, this chapter provides an overview of the components of fiscal federalism in Germany. After providing a brief characterization of the country, we discuss the division of fiscal powers, the possibilities for the different levels of government to generate revenues, and the system of intergovernmental transfers. Besides describing the current situation, we discuss how the latest reform act will change these dimensions of fiscal federalism from 2020 onwards.
Keywords: 330; Finanzbeziehungen; Deutschland